2001
DOI: 10.1002/jctb.487
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preparation method on the catalytic activity of amorphous aluminas in ethanol dehydration

Abstract: The known heterogeneous catalytic dehydration of ethanol on amorphous aluminium oxide samples was adopted as a measure of catalytic activity and selectivity. The aluminium oxide samples were prepared by hydrolysis of aluminium chloride using propylamine, as proton acceptor, in pure and mixed aqueous ethanolic and acetonic media, freeze dried and activated. The catalytic activity and selectivity of the samples was measured in the temperature range 623±698 K for various¯ow rates of ethanol. The apparent activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…21 Our recent study revealed that HB sheets in their hydrogen-deficient state (H : B ratio of approximately 1 : 2.5 AE 0.5) catalyze the conversion of ethanol to ethylene and water above 493 K with high selectivity independent of the contact time, and an apparent activation energy of 102.8 AE 5.5 kJ mol À1 . 22 The activation energy of this process is comparable to those reported for the catalytic dehydration of ethanol over Al 2 O 3 (53-155 kJ mol À1 ), 23,24 the Lewis acidic catalyst Zr-KIT-6 (79 kJ mol À1 ), 25 silica-alumina (125.5 kJ mol À1 ), 26 and the microporous Fe-ZSM-5 (137.7-271.1 kJ mol À1 ). 27 The formation rate of ethylene on the HB catalyst is lower than that offered by state-of-the-art catalysts, but is of the same order as that on the commercial SynDol (Al 2 O 3 -MgO/SiO 2 ) catalyst.…”
Section: Introductionsupporting
confidence: 72%
“…21 Our recent study revealed that HB sheets in their hydrogen-deficient state (H : B ratio of approximately 1 : 2.5 AE 0.5) catalyze the conversion of ethanol to ethylene and water above 493 K with high selectivity independent of the contact time, and an apparent activation energy of 102.8 AE 5.5 kJ mol À1 . 22 The activation energy of this process is comparable to those reported for the catalytic dehydration of ethanol over Al 2 O 3 (53-155 kJ mol À1 ), 23,24 the Lewis acidic catalyst Zr-KIT-6 (79 kJ mol À1 ), 25 silica-alumina (125.5 kJ mol À1 ), 26 and the microporous Fe-ZSM-5 (137.7-271.1 kJ mol À1 ). 27 The formation rate of ethylene on the HB catalyst is lower than that offered by state-of-the-art catalysts, but is of the same order as that on the commercial SynDol (Al 2 O 3 -MgO/SiO 2 ) catalyst.…”
Section: Introductionsupporting
confidence: 72%
“…On the other hand the use of bio-ethanol (bEtOH) as an additive for automobile fuels has increased rapidly all over the World. This is one way of using renewable resources to suppress carbon dioxide emissions, while another challenge is the conversion of bEtOH into various olefins and their use for production of chemicals and polymers [ 1 , 2 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The latter would be very significant for the long-term fixation of carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…EtOH can also react on metal oxide surfaces, to give various chemicals. Acid sites are widely recognized to lead to dehydration of EtOH, giving C2 = , while basic sites lead to dehydrogenation to yield acetaldehyde (AAD) [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. As a result, many kinds of products, for example aldehydes, ketones, C2 = , and C4 = , were observed on oxide catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported a highly active and relatively stable TiO 2 -doped alumina catalyst, and found that the catalyst doped with 10 wt% TiO 2 had higher activities than both undoped alumina and 20 wt% TiO 2 -doped alumina, because 10 wt% Ti/γ-Al 2 O 3 had more moderate acid centres than pure alumina and stronger acidity than 20 wt% Ti/γ-Al 2 O 3 (Chen et al, 2007). Bakoyannakis et al (2001) investigated the effect of the solvent medium on catalytic activity and found that the optimal solvent was pure water, due to its high surface hydroxylation and the presence of an increased number of surface Lewis acid sites. De Boer et al (1967) studied the surface properties of two activated alumina, γ-Al 2 O 3 and η-Al 2 O 3 , which were derived from boehmite and bayerite precursors, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…In order to improve the efficiency of ethylene production via the catalytic ethanol dehydration process, catalysts with higher activity should be developed. Up to now, a large number of catalysts have been studied, which mainly consist of alumina or doped alumina (Bakoyannakis et al, 2001;Clayborne et al, 2004;Domok et al, 2007;Golay et al, 1999;Mitsuo et al, 1981), zeolite (Nguyen and Le Van Mao, 1990;Oudejans et al, 1982), alkali metal oxides or transition metal oxides (Berteau and Delmon, 1989;Di Cosimo et al, 1998;El-Katatny et al, 2000;Zaki, 2005), metal phosphate (Wan and Cheng, 1991), heteropoly acid (Saito and Niiyama, 1987;Varisli et al, 2007) and others. As weak basic centres are needed for dehydration (Roca et al, 1969), most alumina-based catalysts are doped by alkali metal or less acidic metal oxides to obtain high activities.…”
Section: Introductionmentioning
confidence: 99%